Energetics of Sn2+ isomorphic substitution into hydroxylapatite: first-principles predictions. Issue 109 (10th November 2016) - Weck, Philippe F.; Kim, Eunja
Abstract : The energetics of Sn 2+ substitution into the Ca 2+ sublattice of hydroxylapatite, Ca10 (PO4 )6 (OH)2, has been investigated within the framework of DFT. Abstract : The energetics of Sn 2+ substitution into the Ca 2+ sublattice of hydroxylapatite (HA), Ca10 (PO4 )6 (OH)2, has been investigated within the framework of density functional theory. Calculations reveal that Sn 2+ incorporation via coupled substitutions at Ca(ii ) sites is energetically favourable up to a composition of Sn6 Ca4 (PO4 )6 (OH)2, and further substitutions at Ca(i ) sites proceed once full occupancy of Ca(ii ) sites by Sn 2+ is achieved. Compositions of Sn x Ca10− x (PO4 )6 (OH)2 ( x = 4–9) are predominant, with an optimal stoichiometry of Sn8 Ca2 (PO4 )6 (OH)2, and Sn-substituted HA follows approximately Vegard's law across the entire composition range.